Risk management in the Greek mussel farming through ISO 31000 - Theodorou John A.; Tzovenis Ioannis (Oceanological and Hydrobiological Studies)
The main risks to the sustainability of Mediterranean mussel farming in Greece were assessed using a generic framework derived from the AS/NZS ISO 31000:2009 Risk Management Model. Risk management scenarios were reviewed after they were successfully tested in the field by semi-qualitative/quantitative data generation protocols. A critical synthesis of the results identifies key indicative aspects needed by stakeholders to formulate a valid operational risk management plan for the sector.